PROFIT GROWTH OF BANKING COMPANIES LISTED ON IDX: TOTAL ASSET TURNOVER, RISK PROFILE AND GROSS PROFIT MARGIN - Sasmita, Gita Panji; Gupita Dewi, Nurma; Anta Wibawa, Tio (Faculty of Economics and Business University of Mataram, 2023)
This research examines the impact of total asset turnover (TATO), risk profile, and gross profit margin (GPM) on profit growth based on contradictory findings from previous research and fluctuations in banking performance from 2020-2022. This research tested 51 bank samples selected using purposive sampling using bank annual report data published on the IDX. Data were analyzed using multiple linear regression analysis. The research results show that TATO has a significant negative effect on profit growth, while GPM has a significant positive effect on profit growth. On the other hand, the risk profile has a negative and insignificant influence on profit growth. The greater the risk profile of a banking company will indicate a decrease in profit growth due to an increase in non-performing loans. The research implies that bank profit growth is caused by the role of banking intermediation and banks' ability to maintain credit quality and increase operational efficiency.